Meningkatkan Kemampuan Berbicara Melalui Metode Bercakap-cakap Berbantuan Media Audio Visual Pada Kelompok A PAUD Pertiwi I Kota Bengkulu - Mutiara Purnama Sari; Sri Saparahayuningsih; Indrawati Indrawati (Jurnal Ilmiah POTENSIA, 2019)
This research was aimed at improving speaking ability through conversation method via audio visual media. This research is a classroom action research that was conducted in two cycles with three meetings in every cycle. The subjects of this research were group A children consisting of 11 people where there were 5 males and 6 females. For collecting the data, researcher using observation technique was done through observation, while the data analysis was using statistical formula of percentage and mean test. The result of this research proved that through audio-visual media, it can improve the speaking ability. The average of children speaking ability in cycle I has enough criteria, while in cycle II the criteria of children speaking ability was good. From the result of this research, it is suggested for the further researcher to study with the big book and hand puppet media, because with the audio visual media, some children still difficult to utter sounds of language and clarify verbalism